2007
DOI: 10.1177/193229680700100202
|View full text |Cite
|
Sign up to set email alerts
|

Approaches for Improving Glucose Monitor Measurements for Self-Monitoring of Blood Glucose: From Measurement Harmonization to External Quality Assessment Programs

Abstract: Abbreviations: (ADA) American Diabetes Association; (EQA) external quality assessment; (ISO) International Organization for Standardization; (SMBG) self-monitoring of blood glucose Keywords: calibration, device handling, EQA components, external quality assessment, factors affecting measurement variability, harmonization, measurement variability, self-monitoring of blood glucose, specimen collection, standardization AbstractSelf-monitoring of blood glucose (SMBG) is an important component in diabetes manageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 23 publications
(20 reference statements)
0
1
0
Order By: Relevance
“…The most commonly cited problems are incorrect use of the test strip, lack of quality control procedure, fingers that are not clean and dirty devices. Various studies have shown that education and continuous training can reduce errors caused by the aforementioned factors and improve measurement performance [ 115 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most commonly cited problems are incorrect use of the test strip, lack of quality control procedure, fingers that are not clean and dirty devices. Various studies have shown that education and continuous training can reduce errors caused by the aforementioned factors and improve measurement performance [ 115 ].…”
Section: Discussionmentioning
confidence: 99%